2014
DOI: 10.1021/nn505354a
|View full text |Cite
|
Sign up to set email alerts
|

Field Effect Transistors with Current Saturation and Voltage Gain in Ultrathin ReS2

Abstract: We report the fabrication and device characteristics of exfoliated, few-layer, dual-gated ReS2 field effect transistors (FETs). The ReS2 FETs display n-type behavior with a room temperature Ion/I(off) of 10(5). Many devices were studied with a maximum intrinsic mobility of 12 cm(2) · V(-1) · s(-1) at room temperature and 26 cm(2) · V(-1) · s(-1) at 77 K. The Cr/Au-ReS2 contact resistance determined using the transfer length method is gate-bias dependent and ranges from 175 kΩ · μm to 5 kΩ · μm, and shows an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
111
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(139 citation statements)
references
References 33 publications
25
111
3
Order By: Relevance
“…2015, 27, 4640-4648 www.advmat.de www.MaterialsViews.com impact the electronic transport properties of ReS 2 . [ 28 ] However, it is important to note that early reports of MoS 2 CVD growth also exhibited relatively low mobilities, but with further study and optimization of growth, annealing, and contact resistance investigations mobilities improved. [ 6,32 ] Future effort will be put to improve growth and the device fabrication and performance.…”
Section: Communicationmentioning
confidence: 98%
See 1 more Smart Citation
“…2015, 27, 4640-4648 www.advmat.de www.MaterialsViews.com impact the electronic transport properties of ReS 2 . [ 28 ] However, it is important to note that early reports of MoS 2 CVD growth also exhibited relatively low mobilities, but with further study and optimization of growth, annealing, and contact resistance investigations mobilities improved. [ 6,32 ] Future effort will be put to improve growth and the device fabrication and performance.…”
Section: Communicationmentioning
confidence: 98%
“…[ 27 ] This distortion causes symmetry splitting, which could allow the combination of a transistor and an optoelectronic device in a single monolayer. [ 28 ] Previously, 2D ReS 2 has only been synthesized via high temperature (>1000 °C) bulk crystal growth followed by exfoliation in a nonscalable process. [ 25,27 ] Here we demonstrate the fi rst bottom-up method for a scalable synthesis of large-area monolayer ReS 2 .…”
Section: Doi: 101002/adma201501795mentioning
confidence: 99%
“…[18,26,27,64,69,[87][88][89][90][91][92][93] For example, Shim et al [91] , Corbet et al [87,92] and Liu et al [27] reported ReS2-based TFTs with high on/off current ratio of 10 7 , 10 4 and 10 5 , respectively, and Zhang et al [89] and Liu et al [27] demonstrated ReS2-based photodetectors with a photoresponsivity of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 -1 , respectively. Prototypes of ReS2 based FET, photodetector and digital inverter are shown in Figure 10.…”
Section: Electronic and Optoelectronic Device Fabricationmentioning
confidence: 99%
“…[12,96] In addition, atomically smooth surfaces of ReS2 are void of dangling bonds which can significantly reduce the interface state densities and abate the surface roughness scattering. [87] With ReS2 bandgap always remains direct irrespective of bulk to single layers transition as a result of charge decoupling from an extra valence electron in the Re atoms -which causes it to take a distorted 1T crystal structure. It should be noted that other TMDs undergo a direct to indirect transition when the number of layers decreases.…”
Section: Electronic and Optoelectronic Device Fabricationmentioning
confidence: 99%
“…Due to the low lattice symmetry and unique band structures, ReX2 show pronounced in-plane anisotropic properties with possible device applications. For example, few-layer ReX2 sheets have been demonstrated as channel materials for field effect transistors [8,9,11], integrated digital inverters [9] and photodetectors [11,16,17].…”
Section: Introductionmentioning
confidence: 99%